Hadith #737 - Sahih al-Bukhari - Jabir bin 'Atik (Sahih al-Bukhari)
The People of Kufa complained against Sa`d to `Umar and the latter dismissed him and appointed `Ammar as their chief . They lodged many complaints against Sa`d and even they alleged that he did not pray properly. `Umar sent for him and said, “O Aba ‘Is-haq! These people claim that you do not pray properly.” Abu ‘Is-haq said, “By Allah, I used to pray with them a prayer similar to that of Allah’s Apostle and I never reduced anything of it. I used to prolong the first two rak`at of `Is
Grade: Sahih

Hadith #740 - Sahih al-Bukhari - Jabir bin 'Atik (Sahih al-Bukhari)
Sa`d said, “I used to pray with them a prayer similar to that of Allah’s Messenger (ﷺ) (the prayer of Zuhr and `Asr) reducing nothing from them. I used to prolong the first two rak`at and shorten the last two rak`at.” `Umar said to Sa`d “This was what we thought about you.”
Grade: Sahih

Hadith #752 - Sahih al-Bukhari - Jabir bin 'Atik (Sahih al-Bukhari)
`Umar said to Sa`d, “The people complained against you in everything, even in prayer.” Sa`d replied, “Really I used to prolong the first two rak`at and shorten the last two and I will never shorten the prayer in which I follow Allah’s Messenger (ﷺ).” `Umar said, “You are telling the truth and that is what I think a tout you.”
Grade: Sahih

Hadith #2993 - Sahih al-Bukhari - Jabir bin 'Atik (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) said, “When Khosrau is ruined, there will be no Khosrau after him; and when Caesar is ruined, their will be no Caesar after him. By Him in Whose Hands my life is, you will spend their treasures in Allah’s Cause.”
Grade: Sahih

Hadith #3467 - Sahih al-Bukhari - Jabir bin 'Atik (Sahih al-Bukhari)
The Prophet (ﷺ) said, “When Khosrau perishes, there will be no more Khosrau a after him, and when Caesar perishes, there will be no more Caesar after him,” The Prophet (ﷺ) also said, “You will spend the treasures of both of them in Allah’s Cause.”
Grade: Sahih

Hadith #5952 - Sahih al-Bukhari - Jabir bin 'Atik (Sahih al-Bukhari)
A man among us begot a boy whom he named Al-Qasim. The people said, “We will not call him (i.e., the father) by that Kuniya (Abu-l-Qasim) till we ask the Prophet (ﷺ) about it. The Prophet (ﷺ) said. “Name yourselves by my name, but do not call (yourselves) by my Kuniya.”
Grade: Sahih

Hadith #6388 - Sahih al-Bukhari - Jabir bin 'Atik (Sahih al-Bukhari)
The Prophet (ﷺ) said, “If Caesar is ruined, there will be no Caesar after him; and if Khosrau is ruined, there will be no Khosrau, after him; and, by Him in Whose Hand my soul is, surely you will spend their treasures in Allah’s Cause.”
Grade: Sahih

Hadith #6949 - Sahih al-Bukhari - Jabir bin 'Atik (Sahih al-Bukhari)
I heard the Prophet (ﷺ) saying, “There will be twelve Muslim rulers (who will rule all the Islamic world).” He then said a sentence which I did not hear. My father said, “All of them (those rulers) will be from Quraish.”
Grade: Sahih